2011
DOI: 10.1029/2011gl049089
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami source of the 2011 Tohoku-Oki earthquake, Japan: Inversion analysis based on dispersive tsunami simulations

Abstract: [1] The large tsunami of the 2011 Tohoku-Oki earthquake was clearly recorded by the ocean bottom pressure and GPS wave gauges deployed in and around Japan. We estimated the initial tsunami water height distribution by inversion analysis of the waveforms based on dispersive tsunami simulations. The distribution is characterized by a peak height of 8 m located near the trench and the high-water (>2m) region extending landward with a width of ∼100 km. A series of numerical simulations suggests that a relatively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
132
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 143 publications
(140 citation statements)
references
References 23 publications
8
132
0
Order By: Relevance
“…For the 2011 Tohoku-Oki earthquake tsunami, it would be significant to reproduce the tsunami waveform recorded at station 21418, because the record that is located near the source ($500 km) can provide a vast amount of information on the source which is free from distortion caused by the path and site effects. It also shows a clear dispersive wave which can be effectively used for extracting a vast amount of information about the short wavelength component of the source [e.g., Saito et al, 2011;Grilli et al, 2012]. Figure 7 shows the observed and calculated inundation area around the Sendai Plain, which was the widest inundation area for this event.…”
Section: Discussion On the Wave Dispersionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the 2011 Tohoku-Oki earthquake tsunami, it would be significant to reproduce the tsunami waveform recorded at station 21418, because the record that is located near the source ($500 km) can provide a vast amount of information on the source which is free from distortion caused by the path and site effects. It also shows a clear dispersive wave which can be effectively used for extracting a vast amount of information about the short wavelength component of the source [e.g., Saito et al, 2011;Grilli et al, 2012]. Figure 7 shows the observed and calculated inundation area around the Sendai Plain, which was the widest inundation area for this event.…”
Section: Discussion On the Wave Dispersionmentioning
confidence: 99%
“…This source model was characterized by a steep bump higher than 8 m near the trench and characterized by rich short-wavelength components. MacInnes et al [2013] reported that the source model of Saito et al [2011] reproduced the tsunami waveforms recorded at the deep sea better than other models.…”
Section: Tsunami Simulationmentioning
confidence: 99%
See 3 more Smart Citations